Possibility of using green cuttings in vegetative propagation of Sequoiadendron giganteum (Lindl.) J. Buchh.) - Ivanova Valeria; Panchev Valentin; Georgiev Dinko (Agroznanje, 2017)
An experiment was undertaken studying the effects of genotype, treatment with growth regulators and duration of rooting period on the percentage of rooting and quality of the root system of green cuttings of giant sequoia (Sequoiadendron giganteum (Lindl.) J.Buchh.). Cuttings were taken from 18 ten-year seedlings of 10 species of origin. The duration of rooting period (3 months vs. 5 months) was statistically reliable for root-and callus formation rates. The extension of rooting period for two month affords 57.76% more rooted cuttings. The genotype is the main factor influencing the percentage of rooting, number of roots formed and the length of the main root. Treatment with auxin also increase the percentage of rooting, number of roots formed and the length of the main root. Treatment with 4000 ppm indole butyric acid (IBA) gives good results at the end of the third and fourth month, but a five-month rooting period cuttings treated with 4000 ppm IBA showed the highest percentage of rooting.